Urgensi Perlindungan Data Pengguna Financial Technology terhadap Aksi Kejahatan Online di Indonesia - Winnie Stevani; Lu Sudirman (Journal of Judicial Review, 2021)
The ease and sophistication of technology is used as a loophole for illegal persons to carry out their crimes against the personal data of fintech users so that this problem must be positioned as an urgency of legal protection for the privacy rights of each individual. This incident is also supported by the Covid-19 pandemic because all activities must be carried out online. With these problems, this study aims to determine the legal effectiveness of personal data protection in Indonesia and the resolution of the urgency of online crime against the personal data of fintech users. The results of this study indicate that the Indonesian government has not fully realized this crucial theme so that the protection of personal data cannot be carried out optimally by law enforcement officers. Therefore, this research will focus on a description of the importance of personal data protection in Indonesia, the forms of online crimes committed by illegal fintechs, and the resolution of the urgency that arises in the protection of personal data.